2017
DOI: 10.1007/s00270-017-1863-2
|View full text |Cite
|
Sign up to set email alerts
|

Modern Techniques of Lymphangiography and Interventions: Current Status and Future Development

Abstract: One of the crucial functions of the lymphatic system is maintenance of fluid balance. Nonetheless, due to lack of clinical imaging and interventional techniques, the lymphatic system has been under the radar of the medical community. The recently developed intranodal lymphangiography and dynamic contrast-enhanced MR lymphangiography provide new insight into lymphatic pathology. Thoracic duct embolization has become the method of choice for the treatment of patients with chylous leaks. Interstitial lymphatic em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 49 publications
0
68
0
1
Order By: Relevance
“…In addition, it is helpful for planning lymphatic embolization or alternative percutaneous interventions depending on the lymphatic anatomy. [19][20][21] Nadolski et al reported nine patients who underwent DC-MRL in the setting of CA demonstrating lymphatic leakage in seven patients all of which had traumatic etiology. 22 Lymphangiography is an important technique for the detection and treatment of lymphatic leaks.…”
Section: Clinical Complications and Diagnosis Of Chylous Ascitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is helpful for planning lymphatic embolization or alternative percutaneous interventions depending on the lymphatic anatomy. [19][20][21] Nadolski et al reported nine patients who underwent DC-MRL in the setting of CA demonstrating lymphatic leakage in seven patients all of which had traumatic etiology. 22 Lymphangiography is an important technique for the detection and treatment of lymphatic leaks.…”
Section: Clinical Complications and Diagnosis Of Chylous Ascitesmentioning
confidence: 99%
“…Different authors have described several percutaneous approaches to treat refractory ascites with different embolic materials. 20,22,24,25,29,30,[46][47][48][49][50][51][52][53][54][55] INL has been accepted as the gold standard invasive imaging test to delineate the anatomy of the lymphatic system and identify the site of leakage, particularly lymphatic leaks arising from the pelvis, retroperitoneum, and central lymphatics (cisterna chyli and TD). Patients with CA after pelvic lymphadenectomy or retroperitoneal lymphadenectomy (RPLDN) are good candidates for INL alone or associated with glue embolization of the lymph node or lymphatic vessels feeding the leak.…”
Section: Pathways For Lymphangiography and Lymphatic Embolization In mentioning
confidence: 99%
“…The intranodal dynamic MRL (Figure ) evaluates the central conducting lymphatics (usually from the pelvic lymphatics to the site of drainage of the thoracic duct). Since its introduction in clinical practice in the last decade, it has played a crucial role in the understanding and management of CLAs.…”
Section: Recommendationsmentioning
confidence: 99%
“…In both primary and secondary lymphedema of upper and lower limbs, non-contrast magnetic resonance (MR) lymphography has demonstrated its interest for positive diagnosis, evaluation of severity, classification, and follow-up [8,9]. Contrast-enhanced MR lymphangiography may also be performed for analysis of the lymphatic system and is notably useful from a functional point of view (10).…”
Section: Introductionmentioning
confidence: 99%